Hubungan antara Tayangan Akun Tiktok @Liputan6.Com dengan Pemenuhan Kebutuhan Informasi - dizza firnanda listiyanti; Dadi Ahmadi (UNISBA Press, 2022)
Abstract. The previous investigation of this object is to determine the impact of the news transmissions in the account tiktok @liputan6.com in the satisfaction of the information needs of the students. There are four types of information needs, namely the Current need approach, the Everyday need approach, the Exhaustic need approach, and the Catching-up need approach. It takes a way to catch up. This research used types of research include quantitative research using relevant research methods. The main data for this research object were obtained by distributing questionnaires to 82 respondents from the student of Communication Sciences in Bandung Islamic University. The sampling techniques used in the objects studied here currently using simple random sampling techniques. In addition to the reliability test, the data obtained by a single validity analysis is then used. This research object used to have a purpose to determine the relationship between the impression of the tiktok@liputan6.com account and the satisfaction of students' information needs. Abstrak. Penelitian ini dilakukan untuk mengetahui pengaruh tayangan berita pada akun TikTok @Liputan6.com terhadap pemenuhan kebutuhan informasi mahasiswa berdasarkan empat jenis kebutuhan terhadap informasi yaitu Current need approach, Everyday need approach, Exhaustic need approach, Catching-up need approach. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan Studi Korelasional. Data primer pada penelitian ini diambil melalui penyebaran kuisioner kepada 82 responden mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung. Tektik sampling yang digunakan dalam penelitian ini adalah Probably Sampling dengan Teknik Simple Random Sampling. Data yang diperoleh lalu dianalisis dengan menggunakan uni validitas dan uji reliabilitas. Tujuan dari penelitian ini adalah untuk mengetahui Hubungan antara tayangan akun TikTok @Liputan6.com dengan pemenuhan kebutuhan informasi mahasiswa.